2010
DOI: 10.1152/ajpregu.00335.2010
|View full text |Cite
|
Sign up to set email alerts
|

Catestatin in rat RVLM is sympathoexcitatory, increases barosensitivity, and attenuates chemosensitivity and the somatosympathetic reflex

Abstract: Gaede AH, Pilowsky PM. Catestatin in rat RVLM is sympathoexcitatory, increases barosensitivity, and attenuates chemosensitivity and the somatosympathetic reflex. Am J Physiol Regul Integr Comp Physiol 299: R1538 -R1545, 2010. First published October 6, 2010 doi:10.1152/ajpregu.00335.2010.-The fundamental role and corollary effects of neuropeptides that govern cardiorespiratory control in the brain stem are poorly understood. One such regulatory peptide, catestatin [Cts,], noncompetitively inhibits nicotinic-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 45 publications
1
27
0
2
Order By: Relevance
“…This indicates that intrathecal catestatin on its own is not involved in the reflex control of the cardiovascular system. Previously, we reported that microinjection of catestatin into the RVLM increased barosensitivity and attenuated chemosensitivity (13). Differences in injection method, site, and dose may explain this discrepancy.…”
Section: Catestatin Alone Does Not Alter the Tonic Or Reflex Control mentioning
confidence: 89%
See 4 more Smart Citations
“…This indicates that intrathecal catestatin on its own is not involved in the reflex control of the cardiovascular system. Previously, we reported that microinjection of catestatin into the RVLM increased barosensitivity and attenuated chemosensitivity (13). Differences in injection method, site, and dose may explain this discrepancy.…”
Section: Catestatin Alone Does Not Alter the Tonic Or Reflex Control mentioning
confidence: 89%
“…Both peptides are present in nerve terminals that surround SPN, and both peptides exert potent cardiovascular effects elsewhere in the brain but have no effect on blood pressure or reflexes on their own in the spinal cord (9,12,13). A key difference, however, is that catestatin delivered intrathecally does not affect MAP, HR, sSNA, or adaptive reflexes (12).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations